Housing design that improves the independence and safety for older adults using a walker. (November 2021) - Kuboshima, Yukiko; McIntosh, Jacqueline
Abstract: Globally, the walker is one of the most common assistive technologies used by older adults with mobility impairments, which is also the case in New Zealand. However, there is a scarcity of knowledge regarding their specific requirements in housing design. Adopting an ethnographic approach, the perceptions and spatial use of 16 older adults who used a walker were investigated as part of a larger study on quality of life and housing design. Five emergent themes for walker user perception and spatial use were identified, from which design considerations were distilled and then categorised into 10 design elements. The study highlights differences between the requirements for accommodating walkers and those for accommodating wheelchair users. It provides new insights into improved housing design for older adults, which have the potential to be incorporated into existing frameworks for accessible design and universal design thereby improving the independence and safety of older adults. Highlights: Walkers are one of the most commonly used mobility aids by older adults. Existing design guidelines rarely accommodate walkers. A detailed ethnographic survey reveals the difficulties of 16 older adults. Spatial needs for walker users can conflict with those for wheelchair users. Design considerations established need incorporation into accessibility guidelines.